Preventing Atopic Diseases During Childhood – Early Exposure Matters - Pierau, Mandy; Arra, Aditya; Brunner-Weinzierl, Monika C. (Frontiers in Immunology, 2021)
Atopic diseases in childhood are a major burden worldwide and there is still a lack of knowledge about treatable causes. In industrialized countries such as Germany, almost every second child is sensitized to at least one common allergen. Recent studies show that although the predisposition to allergies is inherited, the adaptive immune system of neonates and infants follows a developmental trajectory and whether an allergy actually occurs depends also on timing of allergen exposure including diet as well as environmental factors. New recommendations are far from being rigid of allergen avoidance; it is rather moving towards conditions that stand for more biodiversity. The observation that introduction of peanuts or eggs early in life significantly reduced the development of a later allergy will change our recommendations for the introduction of complementary foods. This is consistent with the hygiene hypothesis that early provocation shapes the developing immune system so that it reacts appropriately. Therefore, promoting the development of tolerance is at the heart of sensible allergy prevention - and this begins with the last trimester of pregnancy. In light of this concept, actual recommendations are discussed.